ANALISIS KASUS TENTANG PERZINAHAN - Samara, Finsensius; Vanessa Altea Talie , Margaretha; J D Djono , Martinus; Marabi Djala, Imanuel Tristan; Manu Bulu , Penta kirania (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This Interrogation Minutes (BAP) contains witness Y.A's statement regarding the alleged crime of adultery that occurred on May 24, 2024 in F.B's boarding house in Atambua, East Nusa Tenggara. Witness Yohanes Aprilianus, as the Chairman of the local RT, was contacted by L.S. and his family to assist in the raid process against R.D.C and I.P. who were suspected of committing adultery. Witness Y.A did not see the incident directly because he was just waiting outside the terrace of the boarding house. However, he heard a statement from L.S. and Veronika Rena who entered the room and saw R.D.C coming out of the room. Witness Y.A also stated that he did not know I.Pdan Febrianti Banu, but knew R.D.C as a family from the same district.